Greatly Enhanced Accessibility and Reproducibility of Worm‐like Micelles by In Situ Crosslinking Polymerization‐Induced Self‐Assembly - Zhang, Wen‐Jian; Chang, Zi‐Xuan; Bai, Wei; Hong, Chun‐Yan (Angewandte Chemie International Edition, 2022)
Worm‐like micelles have attracted great interest due to their anisotropic structures. However, the experimental conditions for obtaining worm‐like micelles are very restricted, which usually causes seriously poor reproducibility. In this work, significantly enhanced accessibility of worm‐like micelles is realized by in situ crosslinking polymerization‐induced self‐assembly (PISA). The reproducibility of worm‐like micelles is greatly improved due to the significantly enlarged experimental windows of worm‐like micelles in the morphology diagram. Moreover, the reliability of the methodology to enhance the accessibility of worm‐like micelles has been demonstrated in various in situ crosslinking PISA systems. The greatly enhanced accessibility and reproducibility of worm‐like micelles is undoubtedly cost‐effective especially in scale‐up production, which paves the way for further application of worm‐like micelles with various compositions and functionalities. Greatly enhanced accessibility of worm‐like micelles (W) is realized by in situ crosslinking polymerization‐induced self‐assembly (PISA), leading to significantly improved reproducibility of worm‐like micelles. The reliability of the methodology has been demonstrated in various in situ crosslinking PISA systems with different formulations of monomers, macro RAFT agents, crosslinkers, solvents, and polymerization temperatures.